A comparative evaluation of fracture resistance of endodontically treated teeth, with variable marginal ridge thicknesses, restored with composite resin and composite resin reinforced with Ribbond: An in vitro study - Vaishali Kalburge; Shaikh Shoeb Yakub; Jitendra Kalburge; Hemalatha Hiremath; Anshu Chandurkar (Wolters Kluwer Medknow Publications, 2013)
Background: The anatomic shape of maxillary premolars show a tendency towards separation of their cusps during mastication after endodontic treatment. Preservation of the marginal ridge of endodontically treated and restored premolars can act as a strengthening factor and improve the fracture resistance. Objectives: To evaluate the effect of varying thickness of marginal ridge on the fracture resistance of endodontically treated maxillary premolars restored with composite and Ribbond reinforced composites. Materials and Methods: One hundred and twenty, freshly extracted, non carious human mature maxillary premolars were selected for this experimental in vitro study. The teeth were randomly assigned in to twelve groups ( n = 10). Group 1 received no preparation. All the premolars in other groups were root canal treated. In subgroups of 3 and 4, DO cavities were prepared while MOD cavities were prepared for all subgroups of group 2, the dimensions of the proximal boxes were kept uniform. In group 3 and 4 the dimensions of the mesial marginal ridge were measured using a digital Vernier caliper as 2 mm, 1.5 mm, 1 mm and 0.5 mm in the respective subgroups. All samples in groups 2.2 and all the subgroups of 3 were restored with a dentin bonding agent and resin composite. The teeth in group 2.3 and all subgroups of 4 were restored with composite reinforced with Ribbond fibers. The premolars were submitted to axial compression up to failure at 45 degree angle to a palatal cusp in universal testing machine. The mean load necessary to fracture was recorded in Newtons and the data was analysed. Results: There was a highly significant difference between mean values of force required to fracture teeth in group 1 and all subgroups of group 2, 3 and 4 (i.e., P < 0.01) Conclusion: On the basis of static loading, preserving the mesial marginal ridge with thicknesses of mm, 1.5 mm, 1 mm and 0.5 mm, composite restored and Ribbond reinforced composite restored maxillary premolars can help preserve the fracture resistance of teeth.